Memorandum of understanding between Universiti Teknologi MARA and Botho University / Fakulti Pengurusan Hotel & Pelancongan - Universiti Teknologi MARA, Fakulti Pengurusan Hotel & Pelancongan (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Botho University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.